1988
DOI: 10.1103/physrevlett.61.1271
|View full text |Cite
|
Sign up to set email alerts
|

Production of a New Light Neutral Boson in High-Energy Collisions

Abstract: Several examples of the production of electron-positron pairs were found in the interactions with emulsion of fragments resulting from the collision of 12 C and 22 Ne projectiles of 4.5 and 4.2 GeV/c per nucleon, respectively with emulsion nuclei. Taking into account the effect of the background, the results seem to suggest the existence of new neutral boson with mass 1.60 ±0.59 MeV/c and a lifetime (0.15±0.01)xl0~1 4 sec.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
29
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 8 publications
2
29
0
Order By: Relevance
“…This result constrains the interpretation of the e *e ~ events seen in emulsions [11,12]. For example, a spinzero Xo with mass 1.14 MeV/c 2 and lifetime 1.3xlO" 15 sec would yield 4700 events in Fig.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…This result constrains the interpretation of the e *e ~ events seen in emulsions [11,12]. For example, a spinzero Xo with mass 1.14 MeV/c 2 and lifetime 1.3xlO" 15 sec would yield 4700 events in Fig.…”
mentioning
confidence: 59%
“…More recently, the production of e + e ~ pairs by heavy ions in emulsion has been presented [11,12] as evidence for new neutral bosons with masses less than 10 MeV/c 2 and lifetimes between 3 x 10 ~1 6 and 1.5 x 10 "' 5 sec.…”
mentioning
confidence: 99%
“…Here, we report the results of neutral boson through the kinematical analysis of 121 measured (e + epairs) found in 200A GeV 32 S interactions with emulsion, as well as pairs from collisions of 12 C and 22 Ne at 4.5A GeV/c [5]. A clear example of 8 events is selected to explain explicitly the production of these pairs in view of the associated projectile fragments having notable charge.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, El-Nadi and Badawy [5] found several experimental results where (e + epairs) were produced in the interactions with emulsion fragments resulting from collision of 12 C and 22 Ne projectiles at ∼ 4.5 GeV/c/nucleon. They used stack of nuclear emulsion rather than using modern electronic detectors joined to a huge heavy ion accelerator.…”
Section: Introductionmentioning
confidence: 99%
“…The general conclusion from these studies has been that no connection exists between the positron peaks observed at GSI and axions [l]. Quite recently we became aware of a nuclear emulsion study [2] where e+e-pairs were reported, which could be due to the decay of light neutral particles. In an independent analysis [3,4] three event clusters appeared around masses of 1.2 (0.2), 2.1 (0.4) and 9.2 (1.2) MeV c -~ and respective lifetimes of 1.3 (0.3) x 3.0 (0.5) x and 6.0 (1.0) x s respectively.…”
mentioning
confidence: 99%